AB0911 REFRACTORY LOW BACK PAIN AND LUMBAR CT-GUIDED STEROID INFILTRATION. STUDY OF 582 PROCEDURES FROM THE SAME CENTER. (June 2019) - Calvo, I.; Ibarguengoitia, O.; Montero, D; Vega, L; María, L; Ruiz, M E.; Torre, I; Fernandez, O; Blanco, J M.; Inchaurbe, A R.; Pérez, Clara; Cuende, Eduardo; et al.
Abstract : Background: Mechanical low back pain which is refractory to analgesic and rehabilitative treatment is an important cause of disability. The primary objective of corticosteroid (CS) lumbar infiltratation is to accelerate the recovery process and to avoid surgery. However, its use is not without controversy. Objectives: To review the indications, efficacy and complications of lumbar computed tomography (CT)-guided CS infiltration. Methods: Retrospective study (January 2012 - April 2018) of lumbar CT-guided CS infiltrations performed in a single center. The epidemiological variables, underlying pathologies, approach of injection, used CS (dexamethasone during the whole period and triamcinolone until February 2015), efficacy after 1 and after 3 months and complications were registered. In addition, a comparative study of the efficacy according to indication, type of CS and approach of injection was performed. Frequencies and percentages were used in qualitative variables, mean±SD in quantitative and for the comparison between groups Chi2 test or Fisher test was used in categorical variables and Student T test or U of Mann-Whitney in quantitative. Statistical analysis was performed with IBM SPSS v.23. Results: 582 procedures were performed in 445 patients (1 infiltration in 445 patients, 2 in 106, 3 in 23, 4 in 7 and 5 in 1). The mean age±SD was 58.6±14.8 years with a male/female ratio of 224/221. Traumatology was the service with highest demand (88.8%) followed by rheumatology (4.8%). The indications were disc herniation (43.1%), lumbar spinal stenosis(36.4%), postoperative fibrosis (14.8%), spondyloarthrosis (2.7%) and other [listhesis, synovial cyst and facet joint syndrome] (2.8%). Posterior epidural access was performed in 27.1% of the procedures, foraminal in 17.9% and lateral recess in 55%. The used CS were dexamethasone (66.3%) and triamcinolone (33.7%). In 86% of patients the oral analgesic treatment had been ineffective. Improvement was observed in 68% of patients at the first month (table) regardless of the indication, approach of injection and CS used and in 63.2% at 3 months. Only 124 patients (21.3%) required surgery due to the persistence of pain, mostly within the first year after infiltration (66.9%). Clinical efficacy showed no statistically significant differences regarding to the indication of the procedure. On the other hand, we observed a significantly higher improvement of the pain through the foraminal and lateral recess than through the epidural at 3 months (p= 0.002). Regarding the CS used, the improvement was significantly greater with triamcinolone compared to dexamethasone in the first and third months (p= <0.001). Concerning safety, there were 16 cases (2.7%) of local complications (5 punctures of the thecal sac, 4 extravasations of the contrast and 7 transient pain in lower extremities) and 5 (0.9%) systemic complications (3 allergic reactions and 2 syncope due to low blood pressure), without clinical relevance and they were not associated with the indication, approach of injection and CS used. Conclusion: In our series disc herniation, lumbar stenosis and postoperative fibrosis were the most common indications. Improvement was observed in 68% and in 63.2% of the patients in the first and third months respectively. Only 21% required surgery. Triamcinolone (although its use is currently discouraged because it is a particulate CS), foraminal infiltration and lateral recess proved to be more effective for pain control. In this study, lumbar CT-guided CS infiltration in patients with refractory low back pain is an accessible, minimally invasive, safe and effective procedure in long term. Disclosure of Interests: None declared